Predicting Future Purchase Intentions In E-Commerce: An Empirical Study On Bukalapak - Arifin Nur Sandi; Sabrina O. Sihombing (Jurnal Manajemen, 2023)
This research explores how consumers' familiarity with a brand and the quality of information they encounter impact their engagement with the brand's social media presence. Additionally, we investigate how this engagement influences consumers' attitudes toward the brand's social media and their intentions for future purchases. This study also delves into the mediating role of social media engagement in the relationship between brand familiarity, information quality, consumers' attitudes toward the brand's social media, and their intentions for future purchases. The research employed a quantitative methodology, specifically purposive sampling, a non-probability approach. Data were collected through online surveys, with 441 samples obtained. The data were analyzed using PLS-SEM with SmartPLS to test hypotheses and draw conclusions. Consequently, all ten hypotheses were validated.